PENGARUH PROFITABILITAS DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN PULP & PAPER YANG TERDAFTAR DI BURSA EFEK INDONESIA - Merlia Triyana Putri; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine effect of profitability and investment decisions on the value of pulp & paper company listed in indonesia stock exchange (IDX). Profitability ratios were used as independent variables is Return On Investment (ROI), Return On Equity (ROE) and the ratio of investment decisions are used ad independent variables is Book Value of The Asset (BVA). While being used as the dependent variable is measured by the value of the company Price Book Value (PBV) listed in Indonesia Stock Exchange (IDX). The methods used to observe the effect of Profitability and Investment decisions on the value of company is by using multiple linear regression.Data used in this study is a secondary data, financial reports (annual report). As for data listed in Indonesia Stock Exchange (IDX) for 6 years from 2009 to 2014. Sampling was done by purposive sampling, used are 5 companies. Analysis data using multiple linear regressions analysis, t test, f test and coefficient of determination test. Analysis data using multiple linear regressions analysis with SPSS 21.The analysis showed that the variable profitability does not significantly affect the value of pulp & paper company listed in the Indonesia Stock Exchange. Whereas investment decision variables did not significantly affect the value of pulp & paper companylisted in Indonesia Stock Exchange. Simultaneous research results showed no significant effect of variable profitability and investment decisions on the value of pulp & paper company listed in Indonesia Stock Exchange (IDX).Keywords : Profitability, Investment Decision, The Value of the Company